Intrahost milieu modulates production of outer membrane vesicles, vesicle-associated Shiga toxin 2a and cytotoxicity in Escherichia coli O157:H7 and O104:H4 - Bauwens, Andreas; Kunsmann, Lisa; Marejková, Monika; Zhang, Wenlan; Karch, Helge; Bielaszewska, Martina; Mellmann, Alexander (Environmental microbiology reports, 2017)
Outer membrane vesicles (OMVs) are important virulence tools of enterohaemorrhagic Escherichia coli (EHEC), but other biological functions of these nanostructures are unknown. We tested the hypothesis that modulation of OMV production enables EHEC to resist the intrahost environment during infection by investigating if simulated human gastrointestinal conditions affect OMV production in EHEC O157:H7 and O104:H4. All the conditions tested including a low pH, simulated ileal and colonic media, presence of mucin, intestinal epithelial cell lysate or antimicrobial peptides, as well as iron limitation, significantly increased OMV production by these pathogens. Accordingly, a maximum vesiculation in EHEC O104:H4 was observed immediately after its isolation from a patient's intestine, and rapidly decreased during passages in vitro. Most of the simulated intrahost conditions also upregulated the OMV-associated Shiga toxin 2a (Stx2a), the major EHEC virulence factor, and, as a result, OMV cytotoxicity. The data indicates that upregulation of OMV production by the human gastrointestinal milieu contributes to EHEC survival and adaptation within the host during infection. Moreover, the intrahost increase of vesiculation and OMV-associated Stx2a may augment EHEC virulence.
Keywords: kultivované buňky; buněčné linie; Cells, Cultured; gastrointestinální trakt; faktory virulence; lidé; Humans; Host-Pathogen Interactions; Virulence; transportní vezikuly; virulence; Escherichia coli Infections; Transport Vesicles; interakce hostitele a patogenu; Gastrointestinal Tract; shiga toxin 2; Escherichia coli O157; infekce vyvolané Escherichia coli; Virulence Factors; Cell Line; Shiga Toxin 2